Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1271/bbb.69.1508
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and Differences between the Characteristics of Gibberellin-Binding Protein and Gibberellin 2-Oxidases in Adzuki Bean (Vigna angularis) Seedlings

Abstract: Gibberellin-binding proteins (GBPs) were purified ca. 230,000 fold. The characteristics of adzuki GBP were examined and compared with those of a recombinant gibberellin 2-oxidase (rVaGA2oxA1) that was fused with glutathione S-transferase (GST). VaGA2oxA1 was most abundantly expressed in etiolated adzuki bean seedlings, and VaGA2oxA1 and GBPs from adzuki bean seedlings showed gibberellin-binding activity when incubated with 2-oxoglutarate and Co 2þ . Both rVaGA2oxA1 and partially purified GBPs from adzuki bean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Nakajima et al (43) also detected GA-binding activity in the soluble protein fraction from adzuki bean (Vigna angularis) seedlings by using a gel-permeation column. Further studies have revealed that this GBP in the partially purified fraction fulfills all four of the GA receptor criteria (47,48).…”
Section: Biochemical Search For the Gibberellin Receptormentioning
confidence: 92%
“…Nakajima et al (43) also detected GA-binding activity in the soluble protein fraction from adzuki bean (Vigna angularis) seedlings by using a gel-permeation column. Further studies have revealed that this GBP in the partially purified fraction fulfills all four of the GA receptor criteria (47,48).…”
Section: Biochemical Search For the Gibberellin Receptormentioning
confidence: 92%
“…(1991) and Gilroy and Jones (1994) have shown that a GA receptor is localized on the plasma membrane of barley aleurone cells, while Nakajima et al. (1997) and Park et al. (2005) suggested that GA‐receptor‐like GA‐binding proteins exist in the cytosolic fraction of adzuki bean seedlings.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to identify the GA receptor have been made using biochemical and genetic approaches. Hooley et al (1991) and Gilroy and Jones (1994) have shown that a GA receptor is localized on the plasma membrane of barley aleurone cells, while Nakajima et al (1997) and Park et al (2005) suggested that GA-receptor-like GA-binding proteins exist in the cytosolic fraction of adzuki bean seedlings. The genetic approach has enabled many mutants with dwarf phenotypes to be isolated and analyzed to identify the genes responsible for the phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…They partially purified GBPs and analyzed the biochemical properties of the proteins. [46][47][48] The bound [ 3 H] 4 -dihydroGA 4 was replaced by nonlabeled GA 4 , suggesting the reversibility of the binding. While it shows a high affinity specific for so called active GAs such as GA 1 , GA 3 , GA 4 , and GA 7 , the binding affinity for GA 9 , GA 8 , and GA 13 is fairly low.…”
Section: Iii1 Research On Cytosolic Gbps In Adzuki Bean (V Angularis) Seedlingsmentioning
confidence: 99%
“…They extensively purified the GBP up to 230,000-fold (Table 2) and examined its biochemical property. 47,48) There remains the possibility that GA 2-oxidase (GA2ox) which selectively catalyzes 2-oxidation of active GAs such as GA 4 and GA 1 shows similar property. They cloned five cDNAs (VaGA2oxA1, A2, VaGA2oxB1, B2 and B3) expressed in adzuki bean seedlings, prepared recombinant VaGA2oxs and examined the enzyme activity and the GA-binding activity (Fig.…”
Section: Iii1 Research On Cytosolic Gbps In Adzuki Bean (V Angularis) Seedlingsmentioning
confidence: 99%